Efeitos antitumorais e antimetastáticos de novos complexos de rutênio em células de câncer de mama - Popolin, Cecília Patricia (2016)
Brazil and the world are passing through demographic changes as consequences of population urbanization, industrialization and advances in science and technology. This process, associated with the transformation of society's quality of life has brought a significant change in the morbidity and mortality profile reducing the occurrence of infectious diseases and increasing incidence of chronic degenerative diseases, like cancer. Cancer is a term used for diseases in which abnormal cells divide without control, and are able to spread and invade other tissues through blood and lymphatic systems. Breast cancer is the second most common cancer in the world and can be considered a cancer with a good prognosis if diagnosed early and treated timely. Treatment of breast cancer has as main objectives to increase survival and improve the quality of life of women. Surgery and radiotherapy are responsible for local control of breast cancer; on the other hand, systemic treatment is made by hormone therapy and chemotherapy. Drugs used in chemotherapy cause resistance and damage to DNA, not only of tumor cells, but also of normal cells. Rosenberg and colleagues in 1964, were responsible for the discovery of antitumor drug to base metals, cisplatin, an effective complex and remains widely used in therapies against various types of tumors, however, despite its effectiveness, also has several side effects. With the limitations of cisplatin, new research has been developed with ruthenium complexes. Ruthenium has some unique properties that can justify their antitumor potential, among them the ability to mimic the iron in connection to many biomolecules, including transferrin and albumin. Therefore, the aim of this study was to evaluate the effect of four new ruthenium complexes with bipyridine and biphophine ligands: (1) [Ru(SO4)(dppb)(bipy)], (2) [Ru(CO3)(dppb)(bipy)], (3) [Ru(C2O4)(dppb)(bipy)] e (4) [Ru(CH3CO2)(dppb)(bipy)]PF6 on the proliferation of breast tumor cells, MDA-MB-231 and MCF-7, and a non-tumor cell line MCF-10A. The results demonstrated that the compound (4) was more efficient inhibiting proliferation of triple negative breast cancer cells MDA-MB- 231, compared with the non-tumor cell line MCF-10A which was more resistant to the complex. Futhermore, the complex (4) was able to reduce the number and size of colonies, to act in the metastatic cascade inhibiting the adhesion, migration and invasion. The complex (4) also inhibited the secretion of MMP9 and induced apoptosis by increasing the expression of pro-apoptotic genes such as Bax and Caspase-3 and decreasing anti-apoptotic genes Bcl-2 in triple negative breast cancer cells, MDA-MB-231. These results show that the complex (4) has potential antitumor and antimetastatic to breast tumor cells; it might be a good alternative drug for the treatment of cancer.